The Importance of Protecting E-Commerce Consumer Personal Data - Itok Dwi Kurniawan; Vincentius Patria Setyawan (CV Tirta Pustaka Press, 2024)
Technological advances offer various conveniences in human daily activities in order to meet their needs. One of the daily human activities that has changed due to the presence of technology is online buying and selling through e-commerce media. Shopping with e-commerce is people's choice because it saves time and costs. However, behind this convenience, attention needs to be paid to the security of consumer data on e-commerce platforms. This article will discuss the importance of protecting personal data from e-commerce consumers. This article was written using a normative type research method with a statutory approach and a conceptual approach. The legal materials used in this research are primary legal materials and secondary legal materials. The technique of collecting legal materials in this research uses literature studies (library research). The legal problem analysis technique used in this research is deductive analysis technique. The results of this research are that personal data security is very necessary in shopping activities in e-commerce, because it is related to consumer satisfaction. When consumers feel safe and are not wary of shopping on e-commerce, they will make shopping on e-commerce a priority compared to shopping conventionally.